Pilot Study of Diagnostic Potential of the Mycobacterium tuberculosis Recombinant HBHA Protein in a Vaccinated Population in Finland - Savolainen, Laura (Public Library of Science, 2008)
BACKGROUND: In recent years T cell based interferon gamma release assays (IGRA) have been developed for immunodiagnosis of M. tuberculosis infection. At present these assays do not discriminate between disease and latency. Therefore, more promising antigens and diagnostic tools are continuously being searched for tuberculosis immunodiagnostics. The heparin binding hemagglutinin (HBHA) is a surface protein of M. tuberculosis which promotes bacterial aggregation and adhesion to non-phagocytic cells. It has been previously assumed that native, methylated form of this protein would be a promising antigen to discriminate latent from active infection. METHODOLOGY AND PRINCIPAL FINDINGS: We performed a pilot investigation to study humoral and T-cell mediated immunological responses to recombinant HBHA produced in M. smegmatis or to synthetic peptides in patients with recent or past tuberculosis, with atypical mycobacteriosis, or in healthy vaccinated individuals. The T cell reactivities to HBHA were compared to the respective reactivities towards Purified Protein Derivative (PPD) and two surface secreted proteins, ie. Early Secretory Antigen Target-6 (ESAT-6) and Culture Filtrate Protein-10 (CFP-10). Our pilot results indicate that methylated recombinant HBHA induced a strong T cell mediated immune response and the production of IgG and IgM-class antibodies in all patient groups, most surprisingly in young Finnish vaccinees, as well. We observed a positive correlation between the reactivities to HBHA and non-specific PPD among all studied subjects. As expected, ESAT-6 and CFP-10 were the most powerful antigens to discriminate disease from immunity caused by vaccination. CONCLUSIONS: On the basis of results of this exploratory investigation we raise concerns that in countries like Finland, where BCG vaccination was routinely used, HBHA utility might not be sufficient for diagnostics because of inability to explicitly discriminate tuberculosis infection from immunoreactivity caused by previous BCG vaccination.